KEAKURATAN BERKAS REKAM MEDIK (STUDI KASUS PADA PASIEN BPJS RAWAT INAP BAGIAN PENYAKIT DALAM RUMAH SAKIT UMUM DAERAH DR PIRNGADI MEDAN TAHUN 2018) - REZA ALFATH; IDARIA SIDABUKKE; DANIEL GINTING (LP2MTBM MAKARIOZ, 2019)
This study was conducted to find out about the accuracy of medical record files in BPJS patients in internal medicine inpatient rooms at Dr Pirngadi Medan Regional General Hospital in 2018. This research is a case study qualitative study. The informants from this study were room nurses and medical record officers. Data collection techniques in research use observation and in-depth interviews. The results showed that it was inaccurate to fill in the medical record files of internal medicine inpatients at the Dr Pirngadi Medan Regional General Hospital because it was often found incomplete in filling patients' medical records, one of which was a diagnosis from a doctor who often missed writing. In addition there has also been a long time to return the patient's medical record status to the medical record section, this is due to several factors such as doctors who have not signed, doctors go out of the city and also seminars so that the return of medical record files is hampered. the assembling section often returns medical records to the room because the doctor's diagnosis with the medication given is not appropriate. Because if it is not suitable between the diagnosis and treatment measures, BPJS cannot clamp it. The results of this study found that filling in the correct medical record of the patient must be in accordance with the procedure. How to deal with so that the medical record is filled in completely should report to the head or section head. Usually socialization will be given and invited to meetings for those concerned.